2012
DOI: 10.1159/000341681
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Aggravating Effects of Nlrp3 Inflammasome Activation in IBD Models: Influence of Genetic and Environmental Factors

Abstract: <b><i>Background:</i></b> Inflammatory bowel disease (IBD) is characterized by chronic intestinal inflammation due to dysregulation of the mucosal immune system. The cytokines IL-1β and IL-18 appear early in intestinal inflammation and their pro-forms are processed via the caspase-1-activating multiprotein complex, the Nlrp3 inflammasome. Previously, we reported that the uptake of dextran sodium sulfate (DSS) by macrophages activates the Nlrp3 inflammasome and that Nlrp3<sup>–/–&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 89 publications
(48 reference statements)
1
95
1
2
Order By: Relevance
“…Studies of murine models of colitis addressing this question, usually of dextran sulfate sodium-induced colitis (DSS-colitis), are inconclusive, since this form of colitis phenocopies human IBD rather poorly, particularly with regard to its dependence on loss of epithelial cell integrity. In any case, in utilizing these models, it has usually been shown that loss-of-function abnormalities of the NLRP3 inflammasome, the main source of IL-1β, are associated with more rather than less intestinal inflammation (20)(21)(22)(23)(24). One possible explanation of this somewhat paradoxical result is that the NLRP3 inflammasome also generates protective factors, such as antiinflammatory cytokines and IL-18, the latter a cytokine that helps maintain epithelial cell integrity and whose absence therefore leads to increased colitis, especially in the DSS-colitis model ly to anti-TNF-α and/or immunosuppressive treatment, but did respond to anakinra or anti-IL-1β antibody administration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of murine models of colitis addressing this question, usually of dextran sulfate sodium-induced colitis (DSS-colitis), are inconclusive, since this form of colitis phenocopies human IBD rather poorly, particularly with regard to its dependence on loss of epithelial cell integrity. In any case, in utilizing these models, it has usually been shown that loss-of-function abnormalities of the NLRP3 inflammasome, the main source of IL-1β, are associated with more rather than less intestinal inflammation (20)(21)(22)(23)(24). One possible explanation of this somewhat paradoxical result is that the NLRP3 inflammasome also generates protective factors, such as antiinflammatory cytokines and IL-18, the latter a cytokine that helps maintain epithelial cell integrity and whose absence therefore leads to increased colitis, especially in the DSS-colitis model ly to anti-TNF-α and/or immunosuppressive treatment, but did respond to anakinra or anti-IL-1β antibody administration.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the peculiarities of biochemical inhibitor studies, including off-target effects versus genetic approaches with altered microbiome, most disease models currently available are susceptible to microbial diversity. In line with this, we have previously reported that cohousing led to comparable susceptibility to colitis-inducing agents in Nlrp3 -/-and WT mice, and that treatment with antibiotics significantly reduced disease severity (30). Intestinal DC comprise multifaceted cell populations with antigen presenting activity, effector T cell stimulation, and induction of Treg differentiation, depending on the local stimulus (31)(32)(33)(34) …”
Section: Introductionmentioning
confidence: 52%
“…Recently, we have reported that the frequency of CD103 + DC in the LP was higher in Nlrp3 -/-mice compared with WT mice at steady state (30). In the present study, we investigated the molecular basis for this observation and elucidated how Nlrp3 links innate to adaptive immune responses in intestinal DC using a T cell transfer colitis model.…”
Section: Cd11bmentioning
confidence: 73%
See 2 more Smart Citations